Development plans and programmes : some case studies and experiences (Geneva : Development Centre of the Organisation for Economics Co-operation and Development, 1962)
This brochure contains the papers presented at the third annual meeting of directors of economic development training institutes. It also includes accounts of the discussions at the end of each paper and the general summing-up of the proceedings established by Prof. Benjamin Higgins.
Includes bibliographical footnotes.
hza 30/01/2019
Loans
Keywords: Economic development; Economic policy